Beckett through Kant: a critique of metaphysical readings - Wilson, Susan (1998)
This thesis calls upon ideas from Immanuel Kant's Critique of Pure Reason to disrupt readings of the plays and prose of Samuel Beckett predicated upon metaphysical presuppositions. The Introduction focuses upon such presuppositions in the criticism of Martin Esslin. In Chapter one, substantial passages of Kantian exposition are given to prepare the ground for a parallel between Kant's critique of metaphysics and those Beckett texts examined through Chapters One, Two, Three and Four. In this first chapter, the limits which Kant places on possible knowledge are compared to the frustrations imposed upon the investigative duo of Beckett's Rough for Theatre II. Chapter Two considers Krapp's Last Tape as a parody of both Proustian and Manichaean metaphysical profundities. Chapter Three examines the consequences of staging the fabrication of a recognizably `Beckettian' image of the human condition in Catastrophe. Chapter Four engages with the textual specifications of The Lost Ones via an ‘immanent' method of analysis, in opposition to `transcendent' or allegorical readings capable of promoting themes of metaphysical import. Chapter Five marks a turning-point in the thesis. It investigates why analysis of The Lost ones should prove as troublesome as it does in Chapter Four. As a response, it details Beckett's efforts toward narrative ‘indetermination' and links this process to the equally troublesome `noumenon of Kant's Critique of Pure Reason. Chapter Six reassesses the parallels drawn between Beckett and Kant thus far. The paradoxes and flat contradictions contained in Chapters One to Four provide the materials for Chapters Six's re-appraisal of the main thesis pursued here, that a critique of metaphysics can be found in Beckett's works analogous to that supplied by Kant. A secondary thesis is that a tendency toward self-defeat during such an interpretation is inevitable. The Conclusion reassesses this contention.